169k views
1 vote
Solve the equation 3 - 2x = 9

a) x = 3
b)x = -3
c) x = 6
d) x = -6

User ErTR
by
5.8k points

2 Answers

4 votes

Answer:


\boxed{\sf (b) \ x = -3}

Explanation:


\sf Solve \: for \: x: \\ \sf \implies 3 - 2x = 9 \\ \\ \sf Subtract \: 3 \: from \: both \: sides: \\ \sf \implies (3 - \boxed{3}) - 2x = 9 - \boxed{3} \\ \\ \sf 3 - 3 = 0 : \\ \sf \implies - 2x = 9 - 3 \\ \\ \sf 9 - 3 = 6 : \\ \sf \implies - 2x = \boxed{6} \\ \\ \sf Divide \: both \: sides \: of \: - 2 x = 6 \: by \: - 2: \\ \sf \implies ( - 2 x)/( - 2) = (6)/( - 2) \\ \\ \sf ( - 2)/( - 2) = 1 : \\ \sf \implies x = - (6)/(2) \\ \\ \sf \implies x = - \frac{3 * \cancel{2}}{ \cancel{2}} \\ \\ \sf \implies x = - 3

User Oliver P
by
4.8k points
5 votes

Answer:

X=-3

Option B is correct ...


solution \\ 3 - 2x = 9 \\ or \: - 2x = 9 - 3 \\ or \: - 2x = 6 \\ or \: x = (6)/( - 2) \\ x = - 3

hope this helps..

Good luck on your assignment...

User Itsmichaelwang
by
5.3k points